An IBBCEAS system for atmospheric measurements of glyoxal and methylglyoxal in the presence of high NO2 concentrations - Jingwei Liu; Xin Li; Yiming Yang; Haichao Wang; Yusheng Wu; Xuewei Lu; Mindong Chen; Jianlin Hu; Xiaobo Fan; Limin Zeng; Yuanhang Zhang (Atmospheric Measurement Technique, 2019)
A system based on incoherent broadband cavity-enhanced absorption spectroscopy (IBBCEAS) has been developed for simultaneous measurement of nitrogen dioxide (NO2), glyoxal (GLY), and methylglyoxal (MGLY). In this system, the measured light absorption at around 460 nm is spectrally resolved. The concentration of absorbers is determined from a multicomponent fit. At an integration time of 100 s, the measurement sensitivity (2 sigma) for NO2, GLY, and MGLY is 18, 30, and 100 ppt, respectively. The measurement uncertainty, which mainly originates from path length calibration, sampling loss, and uncertainty of absorption cross sections is estimated to be 8% for NO2, 8% for GLY, and 16% for MGLY. When deploying the instrument during field observations, we found significant influence of NO2 on the spectra fitting for retrieving GLY and MGLY concentrations, which is caused by the fact that NO2 has a higher absorption cross section and higher ambient concentration. In order to minimize such an effect, a NO2 photolytic convertor (NPC), which removes sampled NO2 at an efficiency of 76 %, was integrated on the IBBCEAS system. Since sampled GLY and MGLY are mostly (>= 95 %) conserved after passing through the NPC, the quality of the spectra fitting and the measurement accuracy of ambient GLY and MGLY under NO2-rich environments could be improved.